Comparison of growth curves with non-linear models in japanese quails of different plumage color - Serdar Guler; Emre Arslan; Muhammet Mucahit Sari; Orhan Cetin (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to estimate growth curve parameters and to determine the best fit model in brown and yellow plumage-colored Japanese quails. Materials and Methods: 80 brown and 80 yellow plumage-colored Japanese quails were used as research material. The quails were weighed 0th, 7th, 14th, 21st, 28th, 35th and 42nd days of age. Gompertz, Logistic, Von Bertalanffy and Richards models were used to determine growth curves. Results: According to the goodness of fit the Gompertz model was determined the best model for both brown and yellow plumage-colored Japanese quails. Coefficient of Determination (R2), Adjusted Coefficient of Determination (R2 adj), Akaike Information Criteria (AIC), Bayesian Information Criteria (BIC) and mean square errors (MSE) were determined 0,9968; 0,9952; 24,8801; 24,7179 and 25,9657 for brown; 0,9975; 0,9963; 22,9149; 22,7527 and 19,6099 for yellow plumage-colored quails, respectively. Parameter ?0, ?1 and ?2 of the model were found 234,89; 3,630; 0,072 & 236,58; 3,516 and 0,069, respectively. The age at point of inflection and weight at point of inflection were calculated 17,91 d and 86,41 g; 18,15 d and 87,03 g for brown and yellow plumage-colored quails, respectively. Conclusion: In conclusion, Gompertz model was determined the best model in this study. This model can be advised to determine the growth curve traits in further researches for different plumage-colored Japanese quails. Morever, Jumbo quail breeding which is a sub-variate of Japanese quail must be considered by quail meat production due to the high maturity index besides the brown plumage-colored Japanese quails.